Effectiveness of technical analysis on Singapore stock market - Low, Chee Khang (2014)
Since the bullish sentiment beginning in 1992 in the Singapore stock market, investment in equity has been a popular topic. The lure for quick profit had attracted many new and less experienced investors to the stock market. Most of these investors are rather unsophisticated in their trading strategies. Among the many approaches adopted by traders in the forecasting of price trend, technical analysis had always been widely acclaimed to be a highly accurate tool. It has proven to be effective in the more developed capital market based on empirical studies. However, its effectiveness in the local context is still uncertain.